O memorial autobiográfico: uma tradição acadêmica do ensino superior no Brasil - Câmara, Sandra Cristinne Xavier da (2012)
The thesis has as object of study the autobiographical memmorials. The general objective is to describe the history of the memmorial as an academic tradition of higher education in Brazil. Considered a hybrid genre, memmorials are known for focusing on life stories from a scientific perspective. The investigation revolves around three intertwined branches: History of Education, educational practices and language usages, which allow us to conduct a dialogue with multiple theoretical-methodological references with a view to supporting our analyses. The corpus used for the analysis was made up of 40 autobiographical memmorials, distributed as follows: 16 academic memmorials, dated from 1935 to 1970; 07 academic memmorials, dated from 1980 to 2007; and 17 formation memmorials, dated from 1995 to 2000. In this corpus, we also included official documents, which relate to legislation contained in edicts, resolutions, ordinances, regulations, which we used with a view to: 1) getting to know and understanding the big picture of higher education regulation in Brazil and the aspects related to the higher education teaching career; 2) investigating the text of memmorials in the light of the injunctive discourse characteristic of the edicts and resolutions in which they were based. The analysis of the memmorial supported by the legislation which regulates it allowed us to reconstitute the image of the professor throughout 80 years in the Brazilian public university. For this purpose, the study was conducted in the theoretical-methodological perspective of the (auto)biographical research in Education and of the sociolinguistic studies on discourse genres and discursive traditions. The investigations reveal the memmorial as an academic genre in which the professor's academic-professional history and the history of the higher education teaching career in Brazil intertwine. Anchored in the Bakhtinian perspective on discourse genres, according to which the memmorials evolve and become more complex as their contexts of usage also evolve and become more complex themselves, the results of our analyses allowed us to correlate genre changes to the sociohistorical context and to its usage as an educational practice in the university, in the decades under study. Therefore, the analyses showed that these self-writings: go from latent subjectivity to pure objectivity from the 1930s to 1960s; they show total annulment of the subject from the 1960s to the 1970s; they reappear in the 1980s, having Professor Magda Soares' memmorial as perspective; they expand and diversify from the 1990s onwards, taking on a formative role and a perspective of future as well. So far as language usages are concerned, we investigated the relationship of the subject with the language, especifically the manifestation of alterity on the discursive tissue of the memmorials. In this branch, the analyses pointed to the influence of the authoritative discourse on the formation of the professor and of the injunction and reinventing discourses on the authorship process. Therefore, the autobiographical memmorial reveals itself as a specific expression of the Brazilian academy's cultural sphere and allows us to confirm the hypothesis that each memorial tackles a singular-plural situation, by presenting a dialectical articulation between private and public, according to the institutional structures, in which and with which the professor has already formed him/herself and with which he/she dialogues